Drug utilization study of antipsychotics among schizophrenia patients in a tertiary care teaching hospital: a retrospective observational study - Mogali, Sahana M.; Kotinatot, Basavaraj C. (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Aim of the study was to evaluate the drug utilization pattern of antipsychotics in schizophrenia patients in a tertiary care hospital. Methods: A retrospective observational study was conducted over a period of one year. Demographic data and drug utilization pattern of antipsychotics was collected from the surveyed prescriptions. Using WHO prescribing indicators data was analysed. Results were expressed in percentage. Results: Out of 300 prescriptions analysed, males were 58% and females 42%. Majority of schizophrenia patients were in age group of 15 to 45 years 70.33%. Olanzapine 75% was most common antipsychotic drug prescribed followed by risperidone 10.7%. Haloperidol 9.6%, fluphenazine 3.7% and chlorpromazine 1% were the other antipsychotics prescribed. Atypical antipsychotics 85.7% were commonly prescribed than conventional ones 4.3%. Concomitant drugs prescribed were anticholinergics, antihistaminics, sedative-hypnotics, antidepressants, mood stabilizers, antiulcer drugs and vitamin B complexes. Average number of drugs prescribed per prescription 3.26. Conclusions: Nowadays atypical antipsychotics are preferred over conventional ones because of their less side effects. Drug utilization study helps in rational usage of drugs important for patient care.